PERAN DINAS PERHUBUNGAN DALAM PERIZINAN ANGKUTAN JALAN (STUDI KASUS BECAK MOTOR DI KOTA SELAT PANJANG TAHUN 2019 -2022) - Hendrizal '; Isril ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The problems that occur in the motorized trishaw public transportation in Selat Panjang city occur due to the emergence of the phenomenon of motorized pedicabs which are mushrooming in the Selat Panjang city and become one of the sources of livelihood for the people of Selat Panjang. This motorized rickshaw has not received more attention from the Selat Panjang City Transportation Agency government agency. Motorized rickshaws in Selat Panjang need attention from related parties because these motorized rickshaws can cause problems that cannot be underestimated, such as traffic accidents, due to a lack of safety standards and passenger safety standards and other matters related to safety when driving in public road. This motorized rickshaw is an alternative transportation that really helps people in the city of Selat Panjang with a cheap and fast fare, so many people choose to use a motorized rickshaw to move from one place to another. Therefore it is necessary to have clear regulations to regulate motorized rickshaws, so that this phenomenon can be minimized. The results of this study show how the role of the Department of Transportation is in controlling and optimizing the phenomenon of motorized rickshaws in the Long Strait. The theory used is the role theory of Biddle and Thomas in Sarwono (2015: 218). This research uses a descriptive method with a qualitative approach. The data analysis technique uses the Sugiono method (2013). The results of this study indicate that the role of the Department of Transportation in licensing motorized pedicab road transport has not gone well. the reason is the lack of coordination between the Department of Transportation, the Police and the Regional Government so that the goals to be achieved have not been realized. Therefore, the researchers suggest that the Meranti Islands Regency Transportation Service coordinate with the police and the Regional Government and carry out routine outreach to motorized pedicab drivers and provide strict action to violators of existing rules. Keyword : interaction in road transport licencin, behavior, operational permit, route permit.